Ecological and Phylogenetic Relationships Shape the Peripheral Olfactory Systems of Highly Specialized Gall Midges (Cecidomiiydae) - Molnár, Béla P.; Boddum, Tina; Hill, Sharon R.; Hansson, Bill S.; Hillbur, Ylva; Birgersson, Göran (Frontiers in Physiology, 2018)
Insects use sensitive olfactory systems to detect relevant host volatiles and avoid un-suitable hosts in a complex environmental odor landscape. Insects with short lifespans, such as gall midges (Diptera: Cecidomyiidae), are under strong selection pressure to detect and locate suitable hosts for their offspring in a short period of time. Ephemeral gall midges constitute excellent models for investigating the role of olfaction in host choice, host shift and speciation. Midges mate near their site of emergence and females migrate in order to locate hosts for oviposition, thus females are expected to be more responsive to olfactory cues emitted by the host compared to males. In this study, we explored the correlation between host choice and the func-tion of the peripheral olfactory system in twelve species of gall midges, including species with close phylogenetic relationships that use widely different host plants and more distantly related gall midge species that use similar hosts. We tested the anten-nal responses of males and females of the twelve species to a blend of 45 known insect attractants using coupled gas chromatographic–electroantennographic detec-tion. When the species-specific response profiles of the gall midges were compared to a newly generated molecular-based phylogeny, we found they responded to the com-pounds in a sex- and species-specific manner. We found the physiological response profiles of species that use annual host plants, and thus have to locate their host every season, are similar for species with similar hosts despite large phylogenetic distances. In addition, we found closely related spe-cies with perennial hosts demonstrated odor response profiles that were consistent with their phylogenetic history. The ecology of the gall midges affects the tuning of the peripheral olfactory system, which in turn demonstrates a correlation between olfaction and speciation in the context of host use.